Change Pattern of Mono and Diacylglycerol in Ethanolysis Reaction of Crude Palm Oil - Asriani Hasanuddin; . Mappiratu; Gatot Siswo Hutomo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
The Changging Pattern of Mono and Diacylglycerol concentration as respon to Reaction time during ethanolysis of Crude Palm Oil was influenced by the ration of ethanol/CPO. By using the ration of 0.25-0.5, the changing pattern of MAG concentration followed the parabolic curve, while that of DAG. By using the ration of ethanol/CPO of 1.5, the change of MAG concentration followed polynomyal curve, while that of DAG followed hyperbolic curve. The changing pattern of MAG dan DAG concentration during ethanolysis reaction of crude palm oil may caused by difference of reactivity and position of fatty acid as well as reactivity of lipid group (TAG, DAG, and MAG) Key Word : Ethanolysis, Monoacylglycerol, Diacylglycerol, crude palm oil.